Chlamydia trachomatis Inclusion Disrupts Host Cell Cytokinesis to Enhance Its Growth in Multinuclear Cells. Issue 1 (January 2016) - Sun, He Song; Sin, Alex T.‐W.; Poirier, Mathieu B.; Harrison, Rene E.
ABSTRACT: Chlamydia trachomatis, the leading cause of bacterial sexually transmitted infections, disrupts cytokinesis and causes significant multinucleation in host cells. Here, we demonstrate that multinuclear cells that result from unsuccessful cell division contain significantly higher Golgi content, an important source of lipids for chlamydiae. Using immunofluorescence and fluorescent live cell imaging, we show that C. trachomatis in multinuclear cells indeed intercept Golgi‐derived lipid faster than in mononuclear cells. Moreover, multinuclear cells enhance C. trachomatis inclusion growth and infectious particle formation. Together, these results indicate that C. trachomatis robustly position inclusions to the cell equator to disrupt host cell division in order to acquire host Golgi‐derived lipids more quickly in multinucleated progeny cells. J. Cell. Biochem. 117: 132–143, 2016. © 2015 Wiley Periodicals, Inc.